Pengaruh Struktur Aktiva terhadap Profitabilitas Perusahaan Subsektor Kontruksi Bangunan dan Subsektor Semen di Indonesia - Emilda Emilda; Gayatri Laila Dwi Sari; Fransiska Romana Eny Fitriani Sihotang; Lulu Aras Desvita (Jurnal Ilmiah Ekonomi Global Masa Kini)
In general, manufacturing companies have larger current assets when compared to fixed assets in the company's asset structure. One of the sub-sectors in manufacturing companies is the construction and building sub-sector. However, it is possible that there is a manufacturing sub-sector that has a fixed asset structure that is more like the cement sub-sector. The purpose of this study is to determine the effect of asset structure on the profitability of the construction and building sub-sector companies, and the cement sub-sector in Indonesia. The data analysis method in this study is the dependent method. The data in this study are 11 companies from the construction and building subsector, and 5 companies from the cement subsector in Indonesia. The variables in this study are the structure of the company's assets and profitability. The results of the study based on the results of the t statistical test (partial test) that the asset structure has a negative effect on the profitability of the cement sub-sector companies in Indonesia, while in the construction and building sub-sector, assets have no effect on profitability as measured by the ROA ratio.Keywords: Asset Structure,  Profitability, the construction and building sub-sector, the cement sub-sector